2018
DOI: 10.1038/s41598-018-21337-6
|View full text |Cite
|
Sign up to set email alerts
|

CD38 promotes pristane-induced chronic inflammation and increases susceptibility to experimental lupus by an apoptosis-driven and TRPM2-dependent mechanism

Abstract: In this study, we investigated the role of CD38 in a pristane-induced murine model of lupus. CD38-deficient (Cd38−/−) but not ART2-deficient (Art2−/−) mice developed less severe lupus compared to wild type (WT) mice, and their protective phenotype consisted of (i) decreased IFN-I-stimulated gene expression, (ii) decreased numbers of peritoneal CCR2hiLy6Chi inflammatory monocytes, TNF-α-producing Ly6G+ neutrophils and Ly6Clo monocytes/macrophages, (iii) decreased production of anti-single-stranded DNA and anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 99 publications
(95 reference statements)
5
34
0
Order By: Relevance
“…The low proportion of pDCs correlated with lower amounts of IFN-α detected in the peritoneal lavage fluids of the Cd38 −/− mice as compared with that in WT and Art2 −/− mice ( Figure 4 c). Indeed, these data are in agreement with our previous study where pristane-treated Cd38 −/− mice showed reduced autoantibody, type I IFN signature, and kidney pathology compared to WT and Art2 −/− mice [ 17 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The low proportion of pDCs correlated with lower amounts of IFN-α detected in the peritoneal lavage fluids of the Cd38 −/− mice as compared with that in WT and Art2 −/− mice ( Figure 4 c). Indeed, these data are in agreement with our previous study where pristane-treated Cd38 −/− mice showed reduced autoantibody, type I IFN signature, and kidney pathology compared to WT and Art2 −/− mice [ 17 ].…”
Section: Resultssupporting
confidence: 93%
“…Although the mechanism is still not fully understood, it seems that IL-10 protects against pristane-induced lung injury by interacting with IL-10R on alveolar macrophages or bone marrow-derived cells [ 16 ]. Cd38 −/− mice develop a milder pristane-induced lupus disease than WT and Art2 −/− mice [ 17 ]. Our data demonstrate that CD38 promotes pristane-induced chronic inflammation and increases susceptibility to experimental lupus by an apoptosis-driven and Transient Receptor Potential Melastatin 2 (TRPM2)-dependent mechanism [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, CD38 deficiency protected mice from the onset of the disease by reducing the number of intraperitoneal apoptotic cells, which are pathogenic in this murine model of SLE. The results of this study suggest that the enzymatic activity of CD38 is important for the regulation of apoptosis in immune cells [27].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 68%
“…Thus, these KO experiments revealed that both CD38 and TRPM2 are involved in the cADPR-and heat-induced facilitation of OT release in vivo. Furthermore, now, cooperative roles of TRPM2 and CD38 were reported in natural killer cells [72], mesenchymal stem cells [73], pancreatic beta cells [74], neutrophil granulocytes [75], and inflammatory monocytes [76]…”
Section: Contribution Of Trpm2 On Ca Signalingmentioning
confidence: 97%